Treatment planning based on water density image generated using dual‐energy computed tomography for pancreatic cancer with contrast‐enhancing agent: Phantom and clinical study. Issue 11 (1st October 2018) - Ohira, Shingo; Yagi, Masashi; Iramina, Hiraku; Karino, Tsukasa; Washio, Hayate; Ueda, Yoshihiro; Miyazaki, Masayoshi; Koizumi, Masahiko; Teshima, Teruki
Abstract : Purpose: A contrast‐enhancing agent is imperative for the accurate target delineation of pancreatic tumors. This study demonstrates the potential use of treatment planning for patients with pancreatic tumors based on the water density image (WDI) generated by dual‐energy computed tomography (DECT). Methods: Tissue characterization and multi‐energy phantom scanning were performed through DECT and the physical characteristics of the WDI and a virtual monochromatic image (VMI) were assessed. The measured and the corresponding theoretical electron density relative to water (RED) and mass density (MD) were compared. Treatment plans based on the WDI (TPWDI ) and VMI (TPVMI ) were compared for 22 pancreatic cancer patients who underwent contrast‐enhanced DECT scan. Results: The total absolute difference in the HU value between the conventional 120 kVp images and the VMI was the smallest at the energy level of 77 keV (3.3 HU), and the VMI at 77 keV was used for subsequent analysis. The difference between the measured and theoretical values of RED and MD for iodine using the VMI (>15%) was larger than that using WDI (<4%). In clinical cases, the maximum difference in the dosimetric parameters between TPWDI and TPWDI for the planning target volume was 3.0% when the doses were calculated using AXB, and for the duodenum, it was 1.7%. Conclusions: The WDI estimated the RED and MD accurately and could form the basis for a new treatment planning approach for pancreatic cancer using contrast‐enhancing agent.